A Green Information Technology governance model for large Mauritian companies. (10th October 2018) - Hardin-Ramanan, Sarita; Chang, Vanessa; Issa, Tomayess
Abstract: Green Information Technology (IT) has emerged as a vital IT governance concern to promote environmentally-friendly IT use and ecologically responsible business processes. Organisational adoption of Green IT is growing in strategic importance, but remains a concern in developing countries, particularly Small Island Developing States (SIDS) such as Mauritius. Despite a strong economic dependence on IT and growing challenges resulting from their environmental vulnerability, the governance of IT and Green IT in SIDS such as Mauritius remains uncharted in existing literature. This study examines IT Governance (ITG) and Green IT in Mauritius by exploring the ITG and Green IT accountabilities, practices and drivers of large Mauritian businesses pertaining to the prime pillars of the Mauritian economy. 109 companies from the population of 192 responded, leading to a response rate of 56.8%. Findings resulting from the exploratory and confirmatory factor analysis of responses were used to develop an IT Governance and Green IT model (ITGM) representing ITG and Green IT accountabilities, mechanisms and drivers among the businesses studied. It is envisaged that the ITGM and its resulting recommendations will provide both Mauritian and other SIDS' companies with a baseline for IT Governance and Green IT practice for improved business IT strategic value. Graphical abstract: Image